2012
DOI: 10.1111/exd.12027
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33 is secreted by psoriatic keratinocytes and induces pro‐inflammatory cytokines via keratinocyte and mast cell activation

Abstract: IL-33 is a novel pro-inflammatory cytokine and ligand for the orphan receptor ST2. Although originally defined as an inducer of Th2-mediated responses, IL-33 was recently found to be involved in arthritis, a Th1/Th17-mediated disease. Here, we assessed the ability of IL-33 to promote inflammation via mast cells (MCs) and keratinocytes (KCs) activation in psoriasis. IL-33 resulted elevated in the skin but not in the serum of psoriasis patients. IL-33 was secreted by psoriasis KCs and HaCaT cells after TNF-a sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 33 publications
8
94
0
Order By: Relevance
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 90%
“…A member of the interleukin-1 receptor (IL-1R)/TLR superfamily, IL-33, has been recognized as a pro-inflammatory molecule that is predominantly expressed in the nucleus of cells with a barrier function, such as endothelial and epithelial cells (23,24). These cells share a common intracellular domain (TIR domain) that may, through MyD88, initiate a signaling cascade, leading to NF-κB translocation (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor (TNF), but not IL-17, stimulates secretion of IL-33, which induces expression of IL-6, monocyte chemoattractant protein-1, and vascular endothelial growth factor (VEGF) (Balato et al, 2012). However, it appears that the type of cytokines/ chemokines produced by IL-33 may depend on the particular tissue since the extent and type of such mediators varies between sensitized skin and asthmatic airways (Savinko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that, we performed experiments in sensitized animals and showed that following DNCB treatment, sensitized K14.E7 skins also displayed significantly enhanced ear swelling, arginase-1 mRNA and arginase activity production compared to non-transgenic skin as observed in non-sensitized mice (Supplementary figure 2.6). Th2 cytokines, which induce arginase-1 expression and hyperinflammatory response in DNCB-treated K14.E7, might therefore be derived from innate immune cells (153,154) or epithelial cells (155). We also detected the induction of prostaglandin E2 synthase in DNCB-treated K14.E7 skin.…”
Section: Discussionmentioning
confidence: 61%